2014
DOI: 10.1260/0263-0923.33.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control for Cubic Strongly Nonlinear Vibration of Automobile Suspension

Abstract: An optimal control method is provided to mitigate the cubic strongly nonlinear vibration of vehicle suspension with velocity and displacement feedback controllers. The forced vibration of the vehicle suspension is studied utilizing the methods of modified Lindstedt-Poincaré and multiple scales. Ranges of feedback gains that can keep the vibration system stable are worked out by the stability conditions of eigenvalue equation. Taking the decay rate and the energy function as the objective functions and the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Observing the previous work done, the nonlinear vibration and control of the amplitude of an automobile system by minimizing energy were studied for under-damped systems. 1 The researchers have also shown that vibration attenuation depends mainly on the damping in a system. 5,12 In vehicle dynamics, the cubic damping ζ is not preferred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observing the previous work done, the nonlinear vibration and control of the amplitude of an automobile system by minimizing energy were studied for under-damped systems. 1 The researchers have also shown that vibration attenuation depends mainly on the damping in a system. 5,12 In vehicle dynamics, the cubic damping ζ is not preferred.…”
Section: Discussionmentioning
confidence: 99%
“…The vehicle dynamics and vibration attenuation of a quarter-car system were investigated by minimizing energy and the effect of damping on the natural frequency and modal damping was studied. 1,2 The optimization of vehicle suspension for ride quality and tyre grip metrics and the optimization, control and stability of the vehicle system were also investigated by researchers. 3,4 The authors studied a shock absorber that attenuates the amplitude of the sprung mass at resonance.…”
Section: Introductionmentioning
confidence: 99%
“…The results layout that the cubic speed input control strategy is effective in lessening the reaction response amplitude of the nonlinear plant just as dispensing with the numerous reactions. Liu et al (2014) controlled the cubic unequivocally nonlinear vibration of vehicle suspension with both speed and displacement feedback controllers by using the adjusted Lindstedt–Poincaré and multiple scale methodology. Amer and Agwa (2019) used two different controlling methods (linear and cubic) of velocity feedback to reduce the mechanical model system’s oscillation that is subjected to parametric forces via the perturbation technique.…”
Section: Introductionmentioning
confidence: 99%
“…25,12 The semi-active concept was also successfully applied to a broad class of vehicle vibration isolation problems, ranging from tractors and other farm vehicles, to high-speed ground transportation vehicles. 1315 Semi-active fluid dampers (oil dampers) are still the most common solution today when large forces are needed and have been widely used in civil engineering structures in Japan. 16 Examples are found for instance in the House of Creation and Imagination of Keio University (Yokohama), completed in 2000, 16 and in the 11-storey Keio University building—Mita South Building erected in 2005.…”
Section: Introductionmentioning
confidence: 99%